An empirical investigation of environmental turbulence and fear in predicting entrepreneurial improvisation - Sara Shabbir; Rizwan Qaisar Danish; Muqqadas Rehman; Muhammad Hasnain Abbas Naqvi; Humaira Asad (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This study is designed to test an empirical investigation of the environmental turbulence and fear in predicting entrepreneurial improvisation in small and medium enterprises (SMEs) in Pakistan. This research aims to analyze whether the emotional response of fear drives the decision-makers of SMEs towards the use of improvisation strategy in a turbulent environment in an uncertain business world or not. The target population for this study includes owners, managers, and directors of SMEs listed in the Chambers of Commerce of capital cities of Pakistan. Data were collected through a quantitative survey from 433 respondents by using the cluster sampling technique. Structural equation modeling (SEM) was used to test the hypotheses of the study and conduct path analysis. The findings of this study reveal that environmental turbulence leads the decision-makers towards the use of improvisation strategy by managing their emotions of fear rather than sticking to the plans in SMEs in Pakistan. Moreover, the emotional response of fear in entrepreneurs mediates the relationship between environmental turbulence and entrepreneurial improvisation in SMEs in Pakistan. This study contributes to the field of SMEs by suggesting that entrepreneurs can compete in the frequently changing business world through improvisation. This study helps the Small and Medium Enterprises Development Authority (SMEDA) to understand the importance of entrepreneurial improvisation during uncertainties in the complex business environment, which leads the organization towards innovation.
Keywords: 650; environmental turbulence; entrepreneurial improvisation; fear; small and mediumenterprises; Pakistan